Postgraduate student-athletes’ narratives of their proposed career paths – in light of an international academic experience - Webster, Brianna (2017)
American student-athletes are subjected to a rigorous schedule, involving rigid heuristics and dogmatic structures that lead many individuals to also perceiving their career to be of that nature. When heading overseas to receive a postgraduate degree in either the United Kingdom or Australia, these individuals experienced a paramount shift in their perception of career and how this relates to the lens in which they view their world. After living overseas, likened to embarking on a ‘hero’s journey’, “the hero lets go of previous unquestioned assumptions and frames of reference, accepts new roles, norms, customs, and schemas (Camptbell, 1996, Inkson, 1997). These participants then returned to the United States with “gift-bestowing hands” and dedicated themselves to giving back to their community in which they currently reside (Britt, 2017, Ch.2, p.33)